Intravenous clomipramine for depressive disorders - Landowski, J; Lamparska, E; Wichowicz, H; Gizińska, D; Godlewska, B; Wiglusz, M (2002)
51 patients with depressive episode (40 - recurrent depressive disorder, 11 - bipolar affective disorder) were treated by the clomipramine intravenous infusions. The number of infusions varied from 5 to 21 (mostly 10-16). The median of maximal dose was 150 mg. There were significant clinical improvement measured by CGI. The therapy was well tolerated.